Moderata Fonte y María Zambrano: por cuenta propia - Rosa Rius Gatell (Universitat de Barcelona, 2010)
In this paper, Rosa Rius thinks about feminine identity and its history, based on the expressions of freedom of two authors living four centuries apart: the Venetian humanist Moderata Fonte (1555-1592) and the Malagan philosopher María Zambrano (1904-1991). The fact that these women’s freedom is taken as one of their main identifying elements, and straining the historical action of this freedom, unforeseen by the establishment, does not at all imply that the undeniable discrimination inflicted upon women throughout centuries is forgotten or goes on without protest.